Maternal Serum Adiponectin Multimers In Gestational Diabetes - Mazaki-Tovi, Shali (2009)
OBJECTIVE: Adiponectin, an adipokine with profound insulin-sensitizing effect, consists of heterogeneous species of multimers. These oligomeric complexes circulate as low-molecular-weight (LMW) trimers, medium-molecular-weight (MMW) hexamers and high-molecular-weight (HMW) isoforms and can exert differential biological effects. The aims of this study were to determine whether there is a change in circulating adiponectin multimers in the presence of gestational diabetes mellitus (GDM), overweight/obesity or with a treatment with sulfonylurea or insulin in patients with GDM. STUDY DESIGN: This cross-sectional study included women with: 1) normal pregnancy (n=149); and 2) patients with GDM (n=72). Thirty three patients with GDM were managed with diet alone. Among the others 39 diabetic patients, 17 were treated with Glyburide and 22 with insulin. The study population was further stratified by first trimester BMI (normal weight <25 kg/m(2) vs. overweight/obese ≥25 kg/m(2)). Serum adiponectin multimers (total, HMW, MMW and LMW) concentrations were determined by ELISA. RESULTS: 1) The median maternal serum of total, HMW, MMW and LMW were lower in patients with GDM than in those with normal pregnancies (p<0.001 for all comparisons); 2) patients with GDM had a lower HMW/Total adiponectin ratio and a higher MMW/Total and LMW/Total adiponectin ratio than those with a normal pregnancy (p<0.001 for all comparisons); and 3) among GDM patients, there were no differences in the concentrations and relative distribution of adiponectin multimers between those who were managed with diet, and those who were treated with pharmacological agents. CONCLUSION: 1) GDM is characterized by a distinctive pattern of concentrations and relative distribution of adiponectin multimers akin to Type-2 diabetes mellitus; 2) dysregulation of adiponectin multimeres can provide a mechanistic basis for the association between adiposity and GDM.